The Effect of Service Failure and Recovery toward Customer Loyalty of Indihome - Al Farisa, Muhammad; Fachira, Ira (Journal of Business and Management, 2016)
Abstract.Nowadays internet is one of the most important necessities in human life. PT Telkom Indonesia comes with indiHome product as the answer of the challenge of this globalization era. indiHome which come with a package of internet, IPTV, and fixed phone succeed to get big number of subscriber, but eventually the reputation of its quality is generates some bad reviews due to the numbers of service failure happened. This research is aimed to assess the effect of service failure happened, and also its recovery by PT Telkom toward the loyalty level of indiHome customer specifically in Bandung area. The data for this research are gathered using questionnaire, and analysed statistically with difference test method. In this research the customer of indiHome are divided into six different groups based on the experience of service failure and recovery which will affect the loyalty. The customer groups are A, customers who never experience service failure, B who have experience service failure which divided into B.1 who get the problem solved, and B.2 who get the problem unsolved. Group B.1 is divided again into B.1.1 who get the outstanding recovery, B.1.2 who get the fair recovery, and B.1.3 who get recovery which is lower than what have been expected.Â The result shows that each group has different level of loyalty. The group of customer who has ever experience service failure and got the outstanding recovery shows the highest score of loyalty level, even exceeding the group of customer who never experience service failure at all. This result of research would contribute to give the recommendation to companies in service industry especially PT Telkom, to put a big concern in designing an outstanding recovery program, and for the academic and research practitioners to take this research for the future researches related.Keywords: Service Failure, Service Recovery, Customer Loyalty, indiHome